Conductivity-Type Sensor Based on CNT-WO3 Composite for NO 2 Detection. (14th April 2008) - Hashishin, Takeshi; Tamaki, Jun
Abstract : The CNTs with 20–50 nm in diameter were directly grown on Au microgap electrode by means of thermal CVD at700 ∘ C for 60 minutes under EtOH-Ar-H 2 atmosphere (6 kPa). The CNTs with entangled shape formed the network structure with contacting each other. In the CNTs-WO 3 composite, WO 3 grains with disk shape (50–200 nm) were independently trapped. The CNTs-WO 3 composite sensor showed the fairly good sensor response (Ra/Rg = 3.8 at200 ∘ C). The sensor response was greatly improved with CNTs-WO 3 composite, comparing with that of CNT sensor (Ra/Rg = 1.05). This phenomenon can be explained by formation of p-n junction, between CNT(p) andWO 3 (n), and thus improvement ofNO 2 adsorption. The sensor response was decreased with increasing theWO 3 amount in CNTs-WO 3 composite, suggesting the electronic conduction due toWO 3 connection.